Dietrich Bonhoeffer’s Relevance for Post-Holocaust Christian Theology - Barnett, Victoria J. (Studies in Christian-Jewish Relations, 2011)
The Protestant theologian and resistance figure Dietrich Bonhoeffer is often portrayed as a hero of the Holocaust, particularly in popular films and literature. Much of the academic literature also assumes a clear relationship between his concern for the Jewish victims of Nazism, his theology, and his participation in the German resistance. A counter-narrative exists, however, which focuses on the anti-Judaism in his writings and contends that a heroic portrait of Bonhoeffer is simplistic and that Bonhoeffer’s significance for post-Holocaust thought is tenuous at best. A key problem here is the volume and complexity of the relevant historical and theological material. The thesis of this essay is that only an in-depth understanding of his theology as a dialogue with the historical complexities of his times can offer insights into his potential contribution to post-Holocaust thought. This essay will review the most salient theological and historical points, focusing on two often overlooked topics: 1) his actual role not only in the German resistance but in the larger ecumenical resistance network that helped Jews across Europe and 2) his own very concrete reflections on guilt, leading to his conviction of the necessity for a different self-understanding among Christians â and a different kind of Christianity â in a post-Nazi world. His experience under Nazism and in the resistance led to a radical reformulation of Christian identity that may be relevant for post-Holocaust theology.